Pipeline implementation of secure hash algorithm (SHA-l) for cryptographic application in network security - Hani, Mohamed Khalil; Sha'ameri, Ahmad Zuri; Chong, Wei Sheng (2000)
This paper presents a pipeline implementation of the Secure Hash Algorithm, SUA-I. This design is targeted for the Altera FlexlOKE50 Field Programmable Gate Array (FPGA) on a PCI card. All input output data interface and internal operations are performed in 32-bit width. The major advantage of this design is the higher throughput gained from the pipeline operations. therefore double speed performance is obtained compared to the equivalent software implementation on Sun SPARC 20/71. The higher throughput shows the potential of this design to support critical network security system, for example the digital signature in e-commerce.